2014
DOI: 10.1007/s00520-013-2071-5
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine for the prevention of bloodstream infection associated with totally implantable venous ports in patients with solid cancers

Abstract: Chlorhexidine topical skin disinfection may prevent PABSI caused by Gram-positive bacteria in patients with solid cancers. The nonsignificant effect on preventing overall PABSI may be attributed to the high incidence of Gram-negative bacteria related PABSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…41 In this regard, a recent study by Kao et al showed that topical skin disinfection with chlorhexidine was associated with a significant improvement in time to first port-a-cath associated BSI in patients with solid tumors compared with disinfection with povidoneiodine. 42 Routine replacement of CVCs and the application of topical antimicrobials in the insertion point are not recommended because they can favor fungal infections and the development of resistance. The use of CVC coated or impregnated with antimicrobials/antiseptics such as chlorhexidine and silver sulfadiazine or minocycline/ rifampin may reduce the risk of infections, although its benefit is relative and its cost is high.…”
Section: Prevention Of Catheter-related Bloodstream Infectionmentioning
confidence: 99%
“…41 In this regard, a recent study by Kao et al showed that topical skin disinfection with chlorhexidine was associated with a significant improvement in time to first port-a-cath associated BSI in patients with solid tumors compared with disinfection with povidoneiodine. 42 Routine replacement of CVCs and the application of topical antimicrobials in the insertion point are not recommended because they can favor fungal infections and the development of resistance. The use of CVC coated or impregnated with antimicrobials/antiseptics such as chlorhexidine and silver sulfadiazine or minocycline/ rifampin may reduce the risk of infections, although its benefit is relative and its cost is high.…”
Section: Prevention Of Catheter-related Bloodstream Infectionmentioning
confidence: 99%
“…They determined that using chlorhexidine reduced the incidence of CoNS-associated CRBSIs. Kao et al 16 detected skin cleansing with chlorhexidine helped to decrease gram-positive bacteria associated CRBSIs in adult patients with solid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Kao ve ark. 'nın [42] yaptığı çalışmada ise solid tümörlü hastalarda kateter bakımında klorheksidin uygulamaları ile özellikle Gram-olumlu mikroorganizmalara bağlı SKİ-KDE hızında azalma rapor edilmiştir.…”
Section: Santral Kateter İlişkili Kan Dolaşımı Enfeksiyonu öNleme Demetiunclassified